An integrated study of the petrographic and geochemical characteristics of organic-rich deposits of the Wufeng and Longmaxi formations, western Hubei Province, South China: Insights into the co-evolution of paleoenvironment and organic matter accumulation. (October 2021) - Zan, Bowen; Mou, Chuanlong; Lash, Gary G.; Ge, Xiangying; Wang, Xiuping; Wang, Qiyu; Yan, Jiaxin; Chen, Feifei; Jin, Bin
Abstract: Enhanced productivity and/or widespread anoxia have been postulated as the dominant controls on organic matter (OM) accumulation in South China during the Ordovician-Silurian (O-S) transition. However, their roles appear to have varied in space and time, and causal mechanisms linking OM accumulation with changing paleoenvironmental conditions remain poorly constrained. Here we report on results of a multi-faceted investigation of the Wufeng and Longmaxi formations in a drilled core from Xianfeng County, western Hubei Province, South China. The roles played by paleoredox conditions, paleoproductivity, paleoclimate, terrigenous input, upwelling, and volcanism on OM accumulation and preservation during the O-S transition are considered. Our results suggest that the depositional history of OM accumulation as recorded by the studied succession can be subdivided into five phases, each one represented by a lithostratigraphic unit. Unit 1 (average TOC = 3.28%) comprises siliceous shale deposited under generally suboxic conditions interrupted by brief episodes of anoxia beneath very productive surface water during the late Katian time (~447.62 Ma). Seasonal upwelling-driven productivity appears to have exerted fist-order control on OM accumulation. Overlying siliceous organic-rich shale of unit 2 (average TOC = 4.93%) records anoxic bottom water conditions from the latest Katian to Hirnantian time. Enhanced productivity and OM preservation may have been maintained by phosphorous cycling. Calcareous shale of the overlying Guanyingqiao unit 3 (TOC = 2.8%) accumulated under suboxic conditions and low to moderate water column productivity during the late Hirnantian Stage. Climate-driven sea level fall was responsible for diminished OM accumulation at this time. Siliceous clay-rich shale of unit 4 (average TOC = 5.53%) was deposited beneath highly productive surface water under anoxic bottom water conditions at the beginning of the Rhuddanian. The presence of volcanic ash and enriched Hg concentrations in these deposits suggests that productivity was enhanced by volcanism. Overlying silty shale of unit 5 (average TOC = 1.71%) was deposited in the middle to upper Rhuddanian under dominantly suboxic conditions, declining productivity levels, and increased delivery of terrigenous sediments. Accumulation of these deposits was contemporaneous with a period of falling sea level related to the Kwangsian Orogeny that would have curbed OM accumulation. Our results, considered in tandem with those of studies from shallow to deep water regions of the Yangtze Block, reveal a level of spatial heterogeneity of redox conditions and productivity levels across the Yangtze Sea during the O-S transition manifested by regional differences in OM accumulation mechanisms and histories. Highlights: Generation of a multi-proxy paleoenvironmental profile of an Ordovician-Silurianorganic-rich shale succession. The history of organic matter (OM) accumulationin studied core can be subdivided into five phases. Hg concentrations are used to consider the contribution of volcanism to OM accumulation. The heterogeneous nature of the marine environment played a major role on regional variations of OM accumulation.